2008
DOI: 10.1136/sti.2008.032425
|View full text |Cite
|
Sign up to set email alerts
|

Patient-initiated delay at a genitourinary medicine clinic: are there public health consequences?

Abstract: Despite 10% of patients choosing to delay attendance beyond 48 h, no adverse public health outcomes were demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In genitourinary (GU) medicine clinics, DNAs may also pose a potential public health risk through the onward transmission of any untreated sexually transmitted infections (STIs). 1–3 In 2006, the UK Department of Health (DH) determined that all patients requesting a GU medicine appointment should be offered such an appointment within 48 hours, and 95% of all patients should be seen within this time. 4,5 Nationally, GU medicine clinics are ‘open access’: booking is unrestricted, and ‘walk-in’ services are offered for those unable or unwilling to attend a clinic appointment.…”
Section: Introductionmentioning
confidence: 99%
“…In genitourinary (GU) medicine clinics, DNAs may also pose a potential public health risk through the onward transmission of any untreated sexually transmitted infections (STIs). 1–3 In 2006, the UK Department of Health (DH) determined that all patients requesting a GU medicine appointment should be offered such an appointment within 48 hours, and 95% of all patients should be seen within this time. 4,5 Nationally, GU medicine clinics are ‘open access’: booking is unrestricted, and ‘walk-in’ services are offered for those unable or unwilling to attend a clinic appointment.…”
Section: Introductionmentioning
confidence: 99%
“…The article by Sanmani et al in this issue ( see page ) adds to the debate by suggesting that the 95% target of patients seen in <48 h is too restrictive 7. Using the precise DH definition, which is that patients should be seen within 2 working days, 8% of their patients seen in the clinic in a 3 month period fell outside of this target access time through personal choice and in reality 10% were seen >48 h if weekends were included.…”
mentioning
confidence: 99%
“…A total of 4.2% of the sample reported unprotected sex with at least one new partner since symptoms had begun. A retrospective review of GUM clinic case notes by Sanmani et al (2008), also in the UK, found that none of the symptomatic patients in their study reported unprotected sex with a new partner after booking their appointment, although it is possible that social desirability bias (the tendency of respondents to answer questions in a manner that will be viewed favourably by others) may have influenced results in this study.…”
Section: Time To Presentationmentioning
confidence: 73%